segundaPRETA: movimento-território-quilombo-artístico-educador em Belo Horizonte - Ana Carolina Martins Lopes (2020)
This work aims at understanding and analyzing the experience of the SegundaPRETA movement, from the viewpoint of the subjects who conceived it and work at it. The SegundaPRETA movement is an initiative carried out by black artists in the city of Belo Horizonte - Minas Gerais, that intends to be a space for elaborations, technical enjoyment and experiments, both in terms of scenic arts as well as other forms of black art production and management. It was born in 2017, from the black artists’ desire to have a space in which they could create, experiment and share artistic knowledge, as well as develop their black art production itself. It arose at first from elaborations in black theater, however, throughout its developments, other forms of art were embraced as well, such as dance, performance and photography. The subjects within this research are seven people: one man and six women. Ethnography was the methodology chosen and carried out in the period from October 2018 to May 2019. The fieldwork was mainly focused on the 7th season of the SegundaPRETA movement, which was held in the months of March and April 2019. In this, two artistic presentations, in particular, were accompanied: the scenic experiment Dor Vestida, by Julhia Santos (BH) and the performance L3n1r4 (Lenira), by Diógenes (RJ). Participant observation, recording in the field journal, collective and individual interviews, images and documentary analysis were the methodological resources adopted. The conclusions of this investigation are the following: the basis for artwork and art creation of the SegundaPRETA movement are black art and antiracism. This political choice can be considered a black insurgency in the artistic and cultural universe of Belo Horizonte. The SegundaPRETA movement, built from collective work in the field of arts, has enabled its members to attain mutual learning, critical positioning in the face of social and racial hierarchies in the realm of arts and culture; the construction of creative, unconventional and political art forms; personal growth in the face of the many challenges, limits, divergences and tensions of collective work; and also the reframing and reaffirmation of black identities. This complex experience is conceptualized by those who conceived it and take part in it as a movement, a territory and a quilombo. After conducting the fieldwork and interviews, this work concludes that two other elements should be added to this triad: an artistic element and an educational element. Therefore, the SegundaPRETA is understood, in this study, as a movement, territory, quilombo, artistic space and educational space in the field of black arts in the city of Belo Horizonte.